1992
DOI: 10.1007/bf00236263
|View full text |Cite
|
Sign up to set email alerts
|

Improved plant regeneration from wheat anther and barley microspore culture using phenylacetic acid (PAA)

Abstract: The effect of the auxin phenylacetic acid (PAA) on wheat anther and on barley anther/microspore culture was investigated. With PAA the induction response was not usually significantly different from controls but a significantly higher number of green plants were produced in wheat anther and barley microspore culture. For wheat anther culture 100 mg/L PAA was beneficial. For barley microspore culture the optimum levels were from 1 to 100 mg/L, depending on genotype. In barley anther culture there were no improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Although the mechanism of albino plant formation is not clear, a molecular analysis of albino wheat plants by Day & Ellis (1984) revealed extensive deletions in their plastomes. Ziauddin et al (1992) reported that the regeneration of green plants from barley microspores was increased 3 times when the auxin p[aenylacetic acid was used in the induction medium. Growth regulators apparently affect the quantity of albino plantlets, and optimizing growth regulator combinations in the culture medium may improve the efficiency of microspore culture.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of albino plant formation is not clear, a molecular analysis of albino wheat plants by Day & Ellis (1984) revealed extensive deletions in their plastomes. Ziauddin et al (1992) reported that the regeneration of green plants from barley microspores was increased 3 times when the auxin p[aenylacetic acid was used in the induction medium. Growth regulators apparently affect the quantity of albino plantlets, and optimizing growth regulator combinations in the culture medium may improve the efficiency of microspore culture.…”
Section: Discussionmentioning
confidence: 99%
“…• 25,000 sugar, sucrose, glucose, and fructose are not suitable for barley androgenesis (Scott and Lyne 1994), whereas maltose alone (Thompson et al 1991, Luckett and Smithard 1992, L0hrs and Nielsen 1992, Pickering and Devaux 1992, Tiwari and Rahimbaev 1992, Ziauddin et al 1992, Salmenkallio-Marttila and Kauppinen 1995 or associated with cellobiose/melibiose (Roberts-Oehlschlager et al 1990, Cai et al 1992, Luckett and Darvey 1992, Pickering and Devaux 1992, has a positive effect on both the androgenetic response and the G/A ratio. Nevertheless, despite the large amount of works, the G/A ratio usually remains lower than 2.…”
Section: Introductionmentioning
confidence: 95%
“…In barley, the most frequent anther pretreatments consist in either a 3-to 5-week thermic stress at 4 ~ (Sunderland and Huang 1985, Lyne et al 1986, Picketing and Devaux 1992, Mordhorst and L6rz 1993 or an osmotic stress by incubating anthers with a nonmetabolizable carbohydrate, e.g., mannitol for 3 days (Roberts-Oehlschlager et al 1990, Ziauddin et al 1990, Hoekstra et al 1992, Luckett and Darvey 1992, Hou et al 1993, Cistu6 et al 1994). The mannitol pretreatment significantly increases the anther response and the G/A ratio, especially in microspore culture (Hoekstra et al 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Profitable effects of PAA have been reported on barley and wheat androgenesis. Ziauddin et al (1992) reported that medium containing PAA has produced a slightly higher embryo than medium containing 2,4-D. They also reported a significant increase in green plant regeneration for wheat anther culture and barely microspores culture by medium containing PAA.…”
Section: The Effect Of Embryo Induction Mediummentioning
confidence: 79%